Optimization of number of scans for a sparse temporal sampling (STS) functional magnetic resonance imaging (fMRI) - Ahmad Nazlim Yusoff; Khairiah Abdul Hamid; Hamdi Hamzah; Mazlyfarina Mohamad; Siti Zamratol Mai Sarah Mukari; Wan Ahmad Kamil Wan Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2016)
High sensitivity signal detection for a sparse temporal sampling (STS) functional magnetic resonance imaging (fMRI) is compensated by the increase in the number of scans (Ns) and consequently the scan time. A long scan time would result in fatigue and restlessness in participants, while a short scan time is undesirable for an STS-fMRI due to insufficient Ns for averaging. The purpose of this study was to determine the Ns practically sufficient for a sparse fMRI study. Eighteen participants were presented with white noise during a sparse fMRI scan. The height extent of activation was determined via t statistics and region of interest (ROI) based percentage of signal change (PSC). The t statistics and PSC for Heschl’s gyrus (HG) and superior temporal gyrus (STG) during which the participants listened to the white noise were calculated for different number of scans which were 6, 12, 18, 24, 30 and 36. The t statistics and PSC values calculated for the bilateral HG and STG qualitatively indicated a minimal change over Ns = 12 to 36. Both ROIs showed a consistent common right lateralization of activation for all Ns, indicating the right-hemispheric dominance of auditory cortex in processing white noise stimulus. It was proposed that for a sparse fMRI study, Ns may practically fall between 12 and 36.